ICT-Based Individualized Training of Institutionalized Individuals With Dementia. Evaluation of Usability and Trends Toward the Effectiveness of the InCoPE-App - Barisch-Fritz, Bettina; Bezold, Jelena; Scharpf, Andrea; Trautwein, Sandra; Krell-Roesch, Janina; Woll, Alexander (Frontiers in Physiology, 2022)
Physical activity interventions can alleviate the course of disease for individuals with dementia (IWD) who have been extraordinarily affected by the COVID-19 pandemic. Information and Communication Technology (ICT) provides new opportunities not only to mitigate negative effects of the pandemic but also to sustainably improve everyday life of IWD in nursing homes. The aim of the present study was to evaluate the ICT-based InCoPE-App, which was used to assess physical and cognitive performance and deliver individualized exercise for IWD, with regard to 1) user experience of nursing assistants, and 2) trends toward the effectiveness of the intervention on physical and cognitive performance of IWD. An 18-week individualized multidomain intervention (2 × 60 min/session) was delivered to an intervention group (IG; n = 10, mean age 88.4 ± 5.6, 70% female) by nursing assistants (n = 10, mean age 56.1 ± 10.4, 90% female) using the InCoPE-App. A control group (CG; n = 3, mean age 87.3 ± 3.5, 100% female) received conventional treatment. User experience was assessed among nursing assistants by different questionnaires, i.e., PSSUQ and ISONORM 9241/110-S for usability, and AttrakDiff2 for pragmatic (PQ), hedonic quality-identity and stimulation (HQI and HQS), and attractiveness (ATT). Trends toward the effectiveness of the intervention were assessed using MMSE (global cognitive function), FICSIT-4 (balance), 6MWT and TUG (mobility), and m30CST (function of lower limbs). Usability of the InCoPE-App was rated as high by nursing assistants (mean ± SD; overall PSSUQ 2.11 ± 0.75; overall ISONORM 9241/110-S 1.90 ± 0.88; ATT 1.86 ± 1.01; PQ 1.79 ± 1.03; HQI 1.8 ± 0.79; and HQS 1.37 ± 0.69). Dropout was high in the total sample (36.7%). Trends toward the effectiveness were observed within IG in nine IWD who showed positive or neutral trends in at least two physical performance outcomes. Seven participants had positive or neutral trends in the FICSIT-4, seven participants in m30CST, and four and seven participants in 6MWT and TUG, respectively. In conclusion, the InCoPE-App has good nursing assistant-rated usability, whereas training effects and intervention adherence were rather low most likely due to COVID-19 restrictions. Single-subject research revealed more positive than negative trends in IG of IWD. Further research is needed to evaluate feasibility, suitability, and effectiveness of the InCoPE-App.